Work hours of employed obstetricians in Taiwan - Ming-Chao Huang; Wen-Chu Huang; Ching-Hung Hsieh; Tsung-Cheng Kuo; Maw-Sheng Lee (Elsevier, 2018)
Objective: Obstetricians have longer work hours and work hour restriction of employed physicians will be implemented thereafter. This study was to survey the impact of work hour restriction and determine the weekly work hours of obstetricians. Materials and methods: Since December 1, 2017, to January 31, 2018, a questionnaire about reasonable workload investigation, impact of work hour restriction and weekly work diary was mailed to 196 employed obstetricians who delivered more than 20 newborns per months. The work types and coefficient of correlation with work hours was evaluated using the Pearson correlation coefficient (r). Results: 72 returned the questionnaires, 21 (31.4%) believed that 40-49 h were reasonable, while 22 (32.8%), 13 (19.4%), 7 (10.4%), and 4 (6%) thought that 50-59, 60-69, 70-79, and >80 h were reasonable. 66 completed their weekly work diary. The average weekly work hours were 80.14 ± 6.85. If the time of awaiting delivery was calculated into total work hours, then the average work hours were 116.96 ± 12.41. The coefficient of correlation between on-duty and weekly work hours was 0.7. The average work hours of physicians with on-duty work were 92.08 ± 8.7, which were significantly higher than the work hours of those without on-duty works (63.95 ± 7.79). Conclusion: The weekly work hours of employed obstetricians is higher than their expected reasonable work hours. Implementation of work hour restriction will have a significant impact on medical care. It is important to determine a reasonable work hour restriction and modify the patient care model to reduce workload. Keywords: Work hour restriction, Employee, Obstetrician